Breathing space : how allergies shape our lives and landscapes - Mitman, Gregg (Yale University Press, 2007)
Breathing Space offers an intimate portrait of how allergic disease has shaped American culture, landscape, and life. Drawing on environmental, medical, and cultural history and the life stories of people, plants, and insects, Mitman traces how America's changing environment from the late 1800s to the present day has led to the epidemic growth of allergic disease. We have seen a neverending stream of solutions to combat allergies, from hay fever resorts, herbicides, and airconditioned homes to numerous potions and pills. But, as Mitman shows, despite the quest for a magic bullet, none of the attempted solutions has succeeded. Until we address how our changing environment -- physical, biological, social, and economic -- has helped to create America's allergic landscape, that hoped for success will continue to elude us. From the dust jacket.